Late Prehistoric Stelae, Persistent Places and Connected Worlds: A Multi-disciplinary Review of the Evidence at Almargen (Lands of Antequera, Spain). Issue 1 (February 2020) - Díaz-Guardamino, Marta; García-Sanjuán, Leonardo; Wheatley, David; Lozano-Rodríguez, José Antonio; Rogerio-Candelera, Miguel Ángel; Casado-Ariza, Manolo
Abstract : This paper examines how monuments with 'local' idiosyncrasies are key in processes of place-making and how, through persistence, such places can engage in supra-local and even 'global' dynamics. Departing from a detailed revision of its context, materiality and iconography, we show how a remarkable Iberian 'warrior' stela brings together the geo-strategic potential of a unique site, located literally between the Mediterranean and the Atlantic worlds, the century-long dialogue between shared and local identities and the power of connectivity of inexorable global processes. Previous approaches to Iberian late prehistoric stelae have had problems in developing bottom-up, theoretically informed and empirically sound approaches to their simultaneously local and supra-local character. The remarkable site of Almargen provides the opportunity to explore this issue. Located in Lands of Antequera (Málaga), a region with a strong tradition of landscape-making through monuments going back to the Late Neolithic, the Almargen 'warrior' stela serves us to explore the notion of 'glocalization', which embodies persistent local engagements with material culture, sites and landscapes on the one hand, and their connections with wider regional and even 'global' worlds on the other.